The Analysis of Pro-Environmental Conservation Attitudes and Behavior Assessment Instruments Upon High School Students Using the Rasch Model - Panjaitan, Sandra Monika; Ningsih, Kurnia; Afandi, Afandi (UIN Fatmawati Sukarno Bengkulu, 2024)
The purpose of this research was to examine the validity and reliability of a questionnaire assessing pro-environmental conservation attitudes and behavior for high school students with 50 statement. Research on pro-environmental conservation attitudes and behavior of secondary school students has probably often been carried out, as was done by Syarief with the title The Role of Geography Learning in Developing Conservation Character of Participants in SMA Negeri 9 Gowa. This research was conducted without using standard instruments to collect data regarding students' attitudes and behavior towards the environment. Research conducted by Lubis et.al entitled Profile of Environmental Concern Attitudes of High School Students in Aceh. This research focuses only on students' caring attitudes towards the environment. Meanwhile, in this study, data collection used standard instruments that had been tested for validity and reliability, and separated attitude indicators from behavioral indicators, so that the focus was not only on pro-conservation attitudes but also on conservation behavior. Statement that were created to measure high school students pro-environmental attitudes and behaviors. The method usin in the research is Research And Development is the approach employed, which alludes to Borg & Gall in Sugiyono (2013). Using simple random selection, 250 high school students from 3 different schools including SMA Negeri 3 Pontianak, SMA Abdi Wacana Pontianak and SMA Kemala Bhayangkari Kubu Raya were used to test the instrument. The findings indicated that the items' validity had been established, as 47 statement items were approved and 3 statement items were refused. Cronbach's alpha value was 0.90, Person Reliability was 0.89, and Item Reliability was 0.97, as determined by reliability analysis. Based on these findings, the instrument for measuring high school students' pro-environmental conservation attitudes and actions may be described as